2017
DOI: 10.1371/journal.pone.0187515
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic diet-induced gut barrier dysfunction and pathobiont expansion aggravate experimental colitis

Abstract: Consumption of a typical Western diet is a risk factor for several disorders. Metabolic syndrome is the most common disease associated with intake of excess fat. However, the incidence of inflammatory bowel disease is also greater in subjects consuming a Western diet, although the mechanism of this phenomenon is not clearly understood. We examined the morphological and functional changes of the intestine, the first site contacting dietary fat, in mice fed a high-fat diet (HFD) inducing obesity. Paneth cell are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 68 publications
8
70
1
Order By: Relevance
“…In addition, while Bacteroidetes Rikenellaceae AF12 taxa were also found to be present in WT gut microbiomes (but < 0.01% compared to Ogg1 -/gut microbiomes and > 5% in Ogg1 -/-HFD), these microorganisms are of note as they have been reported to increase in the gut microbiomes of mouse models exhibiting DSSinduced or spontaneous chronic colitis in comparison to wild-type controls [87]. Finally, Proteobacteria in the Helicobacteriace and Sutterella groups have been reported to be elevated under conditions of DSS-induced colitis [74,88]. It is notable that many of these pro-inflammatory changes were present in chow-fed Ogg1 -/mice and were further exacerbated in HFDfed animals.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, while Bacteroidetes Rikenellaceae AF12 taxa were also found to be present in WT gut microbiomes (but < 0.01% compared to Ogg1 -/gut microbiomes and > 5% in Ogg1 -/-HFD), these microorganisms are of note as they have been reported to increase in the gut microbiomes of mouse models exhibiting DSSinduced or spontaneous chronic colitis in comparison to wild-type controls [87]. Finally, Proteobacteria in the Helicobacteriace and Sutterella groups have been reported to be elevated under conditions of DSS-induced colitis [74,88]. It is notable that many of these pro-inflammatory changes were present in chow-fed Ogg1 -/mice and were further exacerbated in HFDfed animals.…”
Section: Discussionmentioning
confidence: 97%
“…Intestinal permeability was also increased. Mice transplanted with feces from high-fat fed mice were more susceptible to dextran sulfate sodium [DSS]-induced colitis [110]. These studies support (but not prove) a direct pathogenic role of dysbiosis as primary rather than secondary in disease.…”
Section: Escherichia Coli G + Smentioning
confidence: 99%
“…It was demonstrated that the application of an HFD or HF/HSD diets and/or the development of obesity in mice increase(s) the intestinal permeability and bacterial translocation from the intestinal lumen to mesenteric fat, as well as profound changes in the microbiota [102,108,127,181,[184][185][186][187][188][189][190][191][192][193][194][195]. HFD or HF/HSD is also associated with significantly elevated LPS levels, the reduced expression of epithelial tight junction proteins, an increased macrophage infiltration, and the increased expression of proinflammatory biomarkers in the adipose tissue [102,127,181,[184][185][186][187][188][189][190][191][192][193][196][197][198]. Both, the Paneth cell area and the release of antimicrobial factors by Paneth cells are reduced in HFD-fed mice [197].…”
Section: Experimental Studies On Role Of Adipose Tissue In Ibdmentioning
confidence: 99%